MIDWIFERY CARE MANAGEMENT FOR MRS. S WITH SECOND DEGREE PERINEAL TEAR AT SAM CLINIC 2026 - Ompusunggu, Elisabet; Simbolon, Srikandi; Saminah Ginting; Mastaida Tambun; yesika geovani sianipar (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Midwifery care for pregnant women is essential to maintain maternal and fetal health and to prevent complications during pregnancy. During pregnancy, women experience various physiological and psychological changes that may cause discomfort, such as nausea and vomiting, fatigue, back pain, and sleep disturbances. If these conditions are not properly managed, they can reduce the quality of life and increase the risk of complications. In practice, not all pregnant women receive comprehensive and continuous midwifery care according to established standards. This can result in suboptimal management of complaints and delayed detection of complications. The problem in this study is how midwifery care is implemented in managing physiological complaints and preventing complications in pregnant women.Objective: This study aims to describe the implementation of midwifery care for pregnant women at SAM Primary Clinic based on standard care guidelines.Methods: This study used a case study method with a descriptive approach. The subject was a pregnant woman who received care at SAM Primary Clinic. Data were collected through assessment, interviews, physical examinations, and documentation. The care included health education, nutritional counseling, recommendations for adequate rest, and routine antenatal examinations. Data analysis was conducted descriptively to explain the care process and outcomes.Results: The results showed that pregnant women experienced common physiological complaints such as nausea and vomiting, fatigue, back pain, and sleep disturbances, especially in the first and second trimesters. These complaints were managed through health education, balanced nutrition, adequate rest, and regular antenatal care. Monitoring of maternal and fetal conditions showed normal results with no complications during the observation period.Conclusion: Comprehensive and continuous midwifery care using a case study approach is effective in improving maternal and fetal health, managing discomfort, and preventing pregnancy complications.